Clinical, Imaging, Histopathological and Molecular Characterization of Anaplastic Ganglioglioma. Issue 10 (October 2016) - Zanello, Marc; Pages, Mélanie; Tauziède-Espariat, Arnault; Saffroy, Raphael; Puget, Stéphanie; Lacroix, Ludovic; Dezamis, Edouard; Devaux, Bertrand; Chrétien, Fabrice; Andreiuolo, Felipe; Sainte-Rose, Christian; Zerah, Michel; et al.
Abstract : Anaplastic ganglioglioma (AGG) is a rare and malignant variant of ganglioglioma. According to the World Health Organization classification version 2016, their histopathological grading criteria are still ill-defined. The aim of the present study was to assess the clinical, imaging, histopathological, and molecular characteristics and outcomes of AGGs in a large consecutive and retrospective adult and pediatric case series. Eighteen patients with AGGs (13 adults and 5 children) were identified (14 de novo and 4 secondary) from a cohort of 222 gangliogliomas (GG) (8%) treated at our institution between 2000 and 2015. AGGs represented a very aggressive disease with poor outcome (median progression-free survival, 10 months; median overall survival, 27 months). They were located in the temporal lobe only in 22% and presented with seizures (44%) or increased intracranial pressure (44%) at diagnosis. Concerning histopathological and molecular data, they shared morphological characteristics and BRAF V600E mutation (39%) with their benign counterparts but also showed hTERT promoter mutation (61%), p53 accumulation (39%), ATRX loss (17%), or p.K27M H3F3A mutation (17%). AGGs are malignant neoplasms requiring aggressive oncological treatment. In the perspective of targeted therapies, AGGs should be screened for BRAF V600E, hTERT, ATRX, and mutations of histone genes.